2014
DOI: 10.1167/iovs.13-13453
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Lymphatic Vessel Endothelial Hyaluronan Receptor 1 (LYVE1)-Positive Macrophages Around Blood Vessels in the Normal Human Sclera

Abstract: The adult sclera contains blood vessels but lacks, as revealed by immunohistochemistry and confocal microscopy, true lymphatic vessels. LYVE1+ CD68+ macrophages are located adjacent to the longitudinal axis of blood vessels. The function of these cells needs further investigation, but could be a next step toward a better understanding of pathological disorders such as inflammation, tumor, trauma, or glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 37 publications
(39 reference statements)
2
23
0
2
Order By: Relevance
“…Macrophages are often observed in histological sections, being interspersed among lymphatic endothelial cells, especially in tumor-associated lymphatic vessels. A subpopulation of LYVE-1-positive macrophages is reported to be closely related to blood (Schlereth et al 2014) and lymphatic vessels (Gordon et al 2010). All these data should support macrophages as a potential source of lymphatic progenitor cells, but other experimental data showed that LYVE-1-positive macrophages do not express Prox 1 and, thus, are unlikely to be underwent trans-differentiation into lymphatic endothelial cells (Gordon et al 2010).…”
Section: Macrophagesmentioning
confidence: 99%
“…Macrophages are often observed in histological sections, being interspersed among lymphatic endothelial cells, especially in tumor-associated lymphatic vessels. A subpopulation of LYVE-1-positive macrophages is reported to be closely related to blood (Schlereth et al 2014) and lymphatic vessels (Gordon et al 2010). All these data should support macrophages as a potential source of lymphatic progenitor cells, but other experimental data showed that LYVE-1-positive macrophages do not express Prox 1 and, thus, are unlikely to be underwent trans-differentiation into lymphatic endothelial cells (Gordon et al 2010).…”
Section: Macrophagesmentioning
confidence: 99%
“…10 Vascular vessel formation is impaired in T1DM mice. CD31 is a specific marker widely used for vascular vessel identification (15). In the following experiments, CD31 protein levels were detected in the wounded skin of control and T1DM mice.…”
Section: Resultsmentioning
confidence: 86%
“…Similar to the cornea, the sclera and the inner eye are also physiologically devoid of lymphatic vessels, although in direct neighborhood to lymphvascularized tissues [4,31,32]. Lymphatic vessels accompany the extraocular muscles, which insert into the sclera, but lymphatic vessel growth abruptly stops when approaching the sclera.…”
Section: The Lymphatic Vascular Anatomy Of the Eyementioning
confidence: 99%
“…Lymphatic vessels accompany the extraocular muscles, which insert into the sclera, but lymphatic vessel growth abruptly stops when approaching the sclera. The most outer layer of the sclera, the episclera, contains a tight network of blood vessels, which is surrounded by LYVE1+ macrophages [32]. The fetal sclera is also alymphatic but, in contrast to the adult sclera, contains only few macrophages [33].…”
Section: The Lymphatic Vascular Anatomy Of the Eyementioning
confidence: 99%